DNA stable‐isotope probing reveals potential key players for microbial decomposition and degradation of diatom‐derived marine particulate matter. Issue 5 (12th March 2020) - Liu, Ying; Fang, Jiasong; Jia, Zhongjun; Chen, Songze; Zhang, Li; Gao, Wei
Abstract: Microbially mediated decomposition of particulate organic carbon (POC) is a central component of the oceanic carbon cycle, controlling the flux of organic carbon from the surface ocean to the deep ocean. Yet, the specific microbial taxa responsible for POC decomposition and degradation in the deep ocean are still unknown. To target the active microbial lineages involved in these processes, 13 C‐labeled particulate organic matter (POM) was used as a substrate to incubate particle‐attached (PAM) and free‐living microbial (FLM) assemblages from the epi‐ and bathypelagic zones of the New Britain Trench (NBT). By combining DNA stable‐isotope probing and Illumina Miseq high‐throughput sequencing of bacterial 16S rRNA gene, we identified 14 active bacterial taxonomic groups that implicated in the decomposition of 13 C‐labeled POM at low and high pressures under the temperature of 15°C. Our results show that both PAM and FLM were able to decompose POC and assimilate the released DOC. However, similar bacterial taxa in both the PAM and FLM assemblages were involved in POC decomposition and DOC degradation, suggesting the decoupling between microbial lifestyles and ecological functions. Microbial decomposition of POC and degradation of DOC were accomplished primarily by particle‐attached bacteria at atmospheric pressure and by free‐living bacteria at high pressures. Overall, the POC degradation rates were higher at atmospheric pressure (0.1 MPa) than at high pressures (20 and 40 MPa) under 15°C. Our results provide direct evidence linking the specific particle‐attached and free‐living bacterial lineages to decomposition and degradation of diatomic detritus at low and high pressures and identified the potential mediators of POC fluxes in the epi‐ and bathypelagic zones. Abstract : By combining DNA stable‐isotope probing and Illumina Miseq high‐throughput sequencing, we identified 14 bacterial taxonomic groups actively involved in the decomposition of particulate organic matter (POM) at different pressures. Both particle‐attached and free‐living microorganisms were able to decompose POM and assimilate the released dissolved organic matter, suggesting the decoupling between microbial lifestyles and ecological functions. Our results provide direct evidence linking the specific microbial lineages to decomposition and degradation of POM and identified the potential mediators of POM fluxes in the ocean.